Perlindungan Hukum Anak Pasca Pencabutan Hak Asuh Salah Satu Orang Tua - Fauzia Dwianti Nugraha (Jurnal Hukum Lex Generalis, 2025)
One biological parent may have their authority over one or more children revoked for a certain period of time by a court decision. Removing parental control over a child can be done for a number of reasons, such as abuse of authority, grave disregard of responsibilities, misbehavior, and being sentenced for a crime against their child based on a legally enforceable ruling. The Child Protection Law stipulates that parental authority may be revoked or supervision measures may be implemented, that a child may be separated from one parent, that contact between the child and the parent must be permitted, and that care that keeps the child in his family must be prioritized. If the government is given custody of the child, there must be a periodic review to make the separation as short as possible.